Analysis of Operational Form Function for B3C3 Exhibition Hall at Indonesia International Furniture Expo (IFEX) 2023 by PT. Dyandra Promosindo - Priscilla, Mireil (Journal of Indonesian Tourism and Policy Studies, 2025)
Good service can be provided, one of which is by providing operational needs services that are well met for exhibitors, which have been implemented at the IFEX 2023 event. In its implementation, good cooperation is needed in understanding the needs of exhibitors so that everything related to what is needed can be recorded properly and ultimately be used effectively to support the running of the IFEX 2023 event. This study analyzed the role of the Operational Form, especially for exhibitors in the B3C3 area at the IFEX 2023 event. The purpose of this study was to determine how important the role of the 12 forms in the Operational Form is to be a guideline and basis for all exhibitor operational needs information during the IFEX 2023 event. This study uses a qualitative descriptive research type with data collection techniques, namely observation, interviews, and documentation. The source of this research is the database of the IFEX 2023 operational form link. The results of this study indicate that each form contained in the IFEX 2023 Operational Form has its own function that is very influential in the sustainability of the IFEX 2023 event, especially for exhibitor Hall B3C3. It is hoped that the results of this study can provide useful information in the field of managing exhibitor needs, especially needs related to the operations of exhibitors in preparing an event.